The silhouette drawing technique as an assessment of interoceptive awareness - Jokić-Begić, Nataša; Arambašić, Lidija (2010)
Interoception is defined as the sense of the physiological condition of the body and has been suggested to play a key role in the aetiology and maintenance of state and trait anxiety, anxiety sensitivity (AS) and anxiety disorders. This study aimed to investigate whether silhouette drawings technique could be a useful way to assess somatic stress reaction as a measure of interoceptive awareness. The study included a total of 623 adults aged 21 - 71 years. There were 57% of women in the sample. A drawing task was used, which allowed subjects to indicate parts of the body where stress was felt without the imposition of any preconceived ideas by the researcher. On a human body silhouette subjects were asked to indicate the parts of the body where they felt bodily changes during a stressful situation. Associations between total numbers of indicated body parts, anxiety sensitivity, trait anxiety and depression were assessed. Results: Total number of indicated body parts significantly correlated with quantitative measures of anxiety sensitivity, anxiety and depression. Women indicated more body parts then men. Total numbers of indicated body parts is a predictor of anxiety sensitivity above and beyond trait anxiety and depression.The silhouette drawings technique offers an additional way to assess peoples' experience of stress reactions and can improve our knowledge of the interoception.
Projekt MZOS
ENG